Genome analyses suggest recent speciation and postglacial isolation in the Norwegian lemming - Edana Lord; Isabelle S. Feinauer; André E. R. Soares; Vendela K. Lagerholm; Karin Näsvall; Erik Ersmark; Remi-André Olsen; Stefan Prost; Elena A. Kuzmina; Nickolay G. Smirnov; John R. Stewart; Monika V. Knul; et al. (Proceedings of the National Academy of Sciences, 2025)
The Norwegian lemming ( Lemmus lemmus ) is a small rodent distributed across the Fennoscandian mountain tundra and the Kola Peninsula. The Norwegian lemming likely evolved during the Late Pleistocene and inhabited Fennoscandia shortly prior to the Last Glacial Maximum. However, the exact timing and origins of the species, and its phylogenetic position relative to the closely related Siberian lemming ( Lemmus sibiricus ) remain disputed. Moreover, the presence of ancient or contemporary gene flow between both species is largely untested. The Norwegian lemming displays characteristic phenotypic and behavioral adaptations (e.g., coat color, aggression) that are not present in other Lemmus species. We generated a de novo genome assembly for the Norwegian lemming and resequenced nine modern and two ancient Lemmus spp. genomes. We show that all Lemmus species form distinct monophyletic clades, with concordant topology between the mitochondrial and nuclear genome phylogenies. The Siberian lemming is divided into two distinct but paraphyletic clades, one in the east and one in the west, where the western clade represents a sister taxon to the Norwegian lemming. We estimate that the Norwegian and western Siberian lemming diverged shortly before the Last Glacial Maximum, making the Norwegian lemming one of the youngest known mammalian species. We did not find any indication of gene flow between L. lemmus and L. sibiricus , suggesting postglacial isolation of L. lemmus . Furthermore, we identify species-specific genomic differences in genes related to coat color and fat transport, which are likely associated with the distinctive coloration and overwintering behavior observed in the Norwegian lemming.